Recovering Pacific rockfish at risk: the economic valuation of management actions - Forbes, Keldi; Boxall, Peter C.; Adamowicz, W.L. (Vic); De Maio Sukic, Alejandro (Frontiers in Marine Science, 2015)
Over thirty five species of rockfish are found along Canada’s Pacific coast, some of which have been considered for listing under Canada’s Species at Risk Act. We estimate Canadians’ welfare for recovery of a representative Pacific rockfish species using referendum-style stated preference methods administered to a sample of the Canadian public via an internet panel. Hypothetical recovery programs were presented as options to a baseline of current management measures. The programs resulted in varying long term outcomes distinguished by species’ future population projections. An increase in household taxes for a fixed ten year period was employed as the proposed payment mechanism. The econometric analysis found positive and significant welfare measures for all management programs, as well as sensitivity to scope. Willingness to pay ranged from $48 - $180 per year per household depending on the recovery program valued. Welfare measures were found to differ significantly between those who believed their responses to be consequential and those who did not. The former provided measures that were significantly higher than the latter. We conclude with a discussion of the findings in relation to recent literature on consequentiality and incentive compatibility of stated preference questions.